Nursing Procedures in Polyneuropathic Patient - Katarzyna Krystyna Snarska; Cecylia Dolińska; Monika Chorąży (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Polyneuropathy is a condition where multiple sensory and motor nerves are damaged, leading to the development of a number of nuisances. These ailments can, in the long run, lead to a significant reduction in the comfort of our lives. Nurses can have a significant impact on the long-term impact of the disease on the patient through education, support and counseling. Aim. The aim is to illustrate the nature of the problem of polyneuropathy and the importance of care activities in the therapeutic process. Case Report. The presented case study shows a 77-year-old man suffering from type 2 diabetes and polyneuropathy for 17 years. Information about his state of health was obtained on the basis of his own observations, the nurse’s case history, the analysis of the patient’s medical records. The Barthel scale was used to assess the patient’s independence. The assessment of the severity of pain was carried out using the NRS scale. Conclusions. Polyneuropathy is a chronic disease with intensifying symptoms that affect daily life by entangling the underlying disease unit. (JNNN 2022;11(1):31–38)